Memory, Freedom, and Identity: Challenges to “Virtual Consciousness” (Revista Iberoamericana de Bioética, 2024)
This comprehensive text explores the intricate interplay of memory, virtuality, consciousness, and personhood in shaping the human experience. Memory is depicted as a core process integral to identity formation, transcending mere recollection to become a reflective exercise in self-discovery. The advent of the digital age raises concerns about the impact of virtual connections on authentic encounters and the preservation of individual autonomy amid algorithmic homogenizations. In examining consciousness and experience, the inseparability of life and consciousness is emphasized, alongside the significance of corporeality in self-awareness. Abduction is proposed as a mode of creative reasoning that expands our comprehension of the human mind and its relationship with the universe. Furthermore, the text delves into the notion of personhood, highlighting the complexity of identity formation through interaction with the world, others, and history. Through a reflective and pluralistic approach, traditional conceptions of being are challenged, inviting a deeper understanding of the multifaceted human condition.
Keywords: memory; identity; consciousness; virtual; cognition